A Novel Assessment of the Impact of Urban Furniture on Improving Quality of Life and Tourism Development: A Case Study of Kalaleh City - AYOUB BADRAGH NEJAD (اکولوژی انسانی)
This study examines the role and importance of urban furniture in the public spaces of Kalaleh city from the perspective of its citizens. Due to the nature of the subject, the approach of this research combines descriptive-analytical and survey methods. Data were collected through questionnaires completed by residents of various areas of the city. The statistical population of this study includes the citizens of Kalaleh in 2016. Using Cochran's formula, 384 individuals were selected through simple random sampling, and a questionnaire with five options based on the Likert scale was distributed among them. The questionnaire was prepared by the researcher, its face validity was confirmed by experts, and its reliability was verified with a Cronbach's alpha coefficient of 0.85. Hypotheses were tested using one-sample T-tests and Chi-square tests in SPSS software. The results indicate that urban furniture positively impacts the beautification and identity of urban spaces, the physical and mental health of citizens, and the improvement of urban space quality. Furthermore, a positive and significant relationship was observed between urban furniture and attracting tourists, as well as urban tourism development in Kalaleh.